Assessment of Explosive Impact and Methods for Detecting Unmanned Aerial Vehicles During Protection of the Metro Vestibule - Tiutkin, O. L.; Bosyi, D. O.; Sablin, O. I.; Bondarenko, N. K. (Science and Transport Progress, 2025)
Purpose. The authors set the goal of determining the basis for assessing the explosive impact of loitering munitions on the structure of the metro vestibule and developing a method for detecting unmanned aerial vehicles (UAVs) based on information technology. Methodology. The article analyzes two probable scenarios that characterize the strategy of a massive UAV attack. It is noted that these scenarios should be considered not in isolation from each other, but in combination, considering that the probability of a negative scenario is very high, even with the successful implementation of a positive one. The most common design of an underground vestibule (a three-span frame with two rows of columns) is considered. It is shown that an important informative feature of a UAV during flight is acoustic radiation, which allows detecting UAVs in conditions where optical and radar means do not provide the necessary accuracy. A finite element model of the metro vestibule was developed, which was built on the basis of real geometric dimensions using the professional calculation complex Structure CAD. Findings. To solve the first problem (negative scenario), an assessment of the strength of the metro vestibule was carried out. Analysis of the deformed state indicates a normal distribution of all components. It was determined that the equivalent stresses do not reach the design resistance for C25/30 concrete, and the safety margins on average reach 1.7…4.6 times, i.e. the designed structure withstands the combined load from its own weight and explosive load. To solve the second problem (positive scenario), a conceptual scheme for monitoring the condition of ground critical infrastructure objects in the area of ​​laying the metro vestibule with the integration of an air threat detection system is proposed. Originality. The article first assesses the explosive impact of the loitering munition on the structure of the metro vestibule. Based on this assessment, the strength of the reinforced concrete structure of the vestibule as a potential shelter is determined. Practical value lies in the development of a method for detecting unmanned aerial vehicles based on information technology during the protection of the metro vestibule.